STRUGGLE FOR RECONCILIATION IN THE LAST SONG BY NICHOLAS SPARKS - Nafisah Alydrus; Ceisy N. Wuntu; Merlin Maukar (SoCul: International Journal of Research in Social Cultural Issues, 2021)
The purpose of this research is to reveal the struggle to reconcile in Nicholas Sparks The Last Song. In conducting this research, the writers use qualitative research because the data are collected in the form of words and quotations from the primary source which is the novel itself The Last Song written by Nicholas Sparks, and secondary sources are related documents such as books, journal, internet browsing, dictionary, and some materials that can support this research. In analyzing the data, the writers use objective approach to get the information about Steve Miller struggle for reconciliation. The result of research shows the struggle of Steve Miller for reconcile the relationship. In addition, in solving the struggle, the writers conclude in Steve struggle that he did several things, namely by following his daughter's wishes, believing in his daughter, and fighting to hide his illness. Steve Miller gets several effects. Steve Miller more aware of the real love of God, being his daughter aware of Steve's Miller affection, his daughter knows the reason for her parents divorce decision, Making his daughter Peace with Self, and finally they can reconcile the relationship. So, in the struggle it is not easy people need to patient and never give up in facing them. Because there is no struggle without challenges, people must disappointment and tears faced it.